O desenvolvimento profissional docente para a mediação pedagógica das TDICs na educação básica: um estado da questão das produções acadêmicas das IES públicas do Triângulo Mineiro (2007 a 2017) - Araujo, Elaine Aparecida de (2019)
This study, carried out within the scope of the Research Knowledge and Educational Practices Line of the Graduate Program in Education at the Federal University of Uberlândia, sought to investigate how the Professional Teacher Development [Desenvolvimento Profissional Docente – DPD] for the pedagogical mediation of Digital Information and Communication Technologies [Tecnologias Digitais da Informação e Comunicação – TDICs] in basic education was approached and discussed in research developed in public Higher Education Institutions in the Triângulo Mineiro, between the years 2007 and 2017, considering the importance of the active participation of students in the teaching and learning process through the resources provided by the Web 2.0. It is an exploratory study, with a qualitative approach, of bibliographic and documentary type, which sought to understand and reflect on the concepts associated with DPD – Marcelo Garcia (1999, 2009); Melo (2017); Tardif (2014) and Passos et al (2006) –, of pedagogical mediation – Masetto (2013) – and of the pedagogical possibilities of TDICs to stimulate students' creativity, interaction and interactivity through active participation, collaborative production of knowledge and its wide sharing through the world wide web (MORAN, 2007, 2013; PRIMO, 2007; KENSKI, 2013). In addition, we carried out a mapping on the subject of this investigation in the repositories of the CAPES thesis and dissertations catalog, the Brazilian Digital Library of Theses and Dissertations of the Brazilian Institute of Information in Science and Technology (Instituto Brasileiro de Informação em Ciência e Tecnologia – IBICT) and the public/TM higher education institutes in order to we select the research that would be read and analyzed through the construction of a “State of investigation” (THERRIEN and NÓBREGA-THERRIEN, 2004). In this direction, we seek to describe and analyze the theoretical-methodological approaches and the main notes of the selected studies on the continuing education of teachers for the pedagogical mediation of TDICs in basic education from 2007 to 2017. The main results of the investigation allow us to conclude that, despite the investments for the inclusion of public schools of basic education in digital culture and for the continuous training of teachers for the pedagogical use of TDICs, the lack of articulation between theory and practice in training actions has impaired the critical, conscious and autonomous training of teachers for the pedagogical mediation of digital technologies in basic education. Furthermore, most of the selected researches presented training proposals and/ or bibliographic researches that are alingned with the perspective of teaching professional development. In other words, these researchers believe in the teacher's critical-reflective training concept and point out that the training proposals must consider the training needs of teachers and happen in a permanent, continuous and contextualized way, in addition to promoting the autonomy and reframing of teaching practices for that the pedagogical mediation of TDICs in basic education favors the students' significant learning.